2009
DOI: 10.3988/jcn.2009.5.4.178
|View full text |Cite
|
Sign up to set email alerts
|

Increased EEG Current-Source Density in the High Beta Frequency Band Induced by Levetiracetam Adjunctive Therapy in Refractory Partial Epilepsy

Abstract: Background and PurposeLevetiracetam (LEV) is an antiepileptic drug (AED) that has favorable effects on cognition. Although neuropsychological studies have demonstrated these favorable outcomes on cognition, there are few electrophysiologic data describing the functional changes exerted by LEV. The purpose of this study was to determine the effects of LEV adjunctive therapy on the current-source density (CSD) in the high beta frequency band (22-30 Hz) of EEG background activity in refractory partial epilepsy (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 40 publications
0
13
2
Order By: Relevance
“…In our previous study, the CSD of the high beta frequency band increased in the bilateral anterior cingulate gyri, left parahippocampal gyrus, and a small area of the right anterior parahippocampal gyrus after a 24-week levetiracetam (LEV) trial in patients with refractory partial epilepsy. In the previous study, verbal memory and executive function improved 26. In contrast, the CSD of the high beta frequency band decreased in the superior frontal, middle frontal, anterior cingulate, precentral, postcentral, and inferior parietal gyri of the left hemisphere, and the middle frontal, inferior frontal and anterior cingulate gyri of the right hemisphere after the 24-week ZNS trial in the present study.…”
Section: Discussioncontrasting
confidence: 50%
“…In our previous study, the CSD of the high beta frequency band increased in the bilateral anterior cingulate gyri, left parahippocampal gyrus, and a small area of the right anterior parahippocampal gyrus after a 24-week levetiracetam (LEV) trial in patients with refractory partial epilepsy. In the previous study, verbal memory and executive function improved 26. In contrast, the CSD of the high beta frequency band decreased in the superior frontal, middle frontal, anterior cingulate, precentral, postcentral, and inferior parietal gyri of the left hemisphere, and the middle frontal, inferior frontal and anterior cingulate gyri of the right hemisphere after the 24-week ZNS trial in the present study.…”
Section: Discussioncontrasting
confidence: 50%
“…19 – 21 ) Other studies have used similar neuropsychological tests to measure such executive functions. 22 , 23 ) Software developed in our own laboratory (DELPHI 5.0) was used to analyze the reaction time. Participants had to choose a square (25% of total shapes) among various circles, identifying the reaction time.…”
Section: Methodsmentioning
confidence: 99%
“…One recent report stated that LEV therapy increases the 22–30 Hz band of EEG background activity in the bilateral anterior cingulate and left parahippocampal gyri of patients with refractory partial epilepsy, and that this change is associated with improvements in verbal memory and executive function. 16 LEV has also been shown to decrease delta and theta power in the frontopolar and anterior areas, increase alpha2 in diffuse areas, and increase beta2 in the left temporal area. 17 …”
Section: Discussionmentioning
confidence: 94%
“… 14 LEV does not negatively influence cognitive function and may even improve it. 15 EEG studies have reported that LEV has a positive effect on cerebral neuronal activity and cognitive function; 16 , 17 however, these studies investigated only the long-term effects of LEV, and changes in cerebral glucose metabolism were not assessed.…”
Section: Introductionmentioning
confidence: 99%